APPLICATION of SBA-Pr-SO3H IN THE GREEN SYNTHESIS OF ISATINHYDRAZONE DERIVATIVES: CHARACTERIZATION, UV-Vis INVESTIGATION AND COMPUTATIONAL STUDIES - Gholamzadeh, Parisa; Mohammadi Ziarani, Ghodsi; Badiei, Alireza (Journal of the Chilean Chemical Society, 2016)
An efficient and green synthesis is developed for the preparation of the arylidene isatinhydrazone derivatives 4a-m using a heterogeneous mesoporous acid catalyst of SBA-Pr-SO3H with a pore size of 6 nm under solvent free conditions. The hydrazones 4a-m were then analyzed by UV-Vis spectroscopy and the results were used for the calculation of the HOMO-LUMO band gap. In addition, the quantum chemical calculations were performed to provide an illustrative explanation for the obtained band gap; it is found that probably these molecules have a high tendency to donate electrons to the appropriate small-molecule acceptors with low energy and empty molecular orbital.